Ligninolytic enzymes profiling in association with the aggressiveness of Ganoderma boninense isolates - Periasamy, Gunashila; Yun, Wong Mui; Vadamalai, Ganesan; Ling, Ho Chai; Naidu, Yuvarani Raja; Sundram, Shamala (Universiti Sains Malaysia, 2023)
Aims: This study was designed to examine the enzyme activity of selected virulent isolates of Ganoderma boninense against oil palm. In a separate in vitro assessment, the effect of macronutrients on the mycelial growth of four selected Ganoderma spp. was also tested. Methodology and results: The study involved a comparison of ligninolytic enzymes; lignin peroxidase (LiP), manganese peroxidase (MnP) and laccase (Lac) profiling of eight isolates of G. boninense, categorized into three levels of aggressiveness, with two control isolates (G. boninense PER71 and G. tornatum NPG1) using solid-state fermentation (SSF). The Principal Component Analysis (PCA) revealed that the isolates had a significant production of ligninolytic enzymes on day 80. The most aggressive isolate, ET61 had the highest Lac production. As for the macronutrient test, mycelial growth for all the Ganoderma spp. was highly affected by potassium (K). Conclusion, significance and impact of study: The findings of this study elucidated the characteristics of G. boninense in relation to enzyme production for the degradation of oil palm lignin and the identification of essential nutrients involved in the survival and growth of Ganoderma spp. The study provides vital information on the pathogenic characteristics of G. boninense isolates involved in biomass degradation along with the role of nutrient on the growth of Ganoderma spp. that may influence basal stem rot (BSR) management in the field.